Paridis Rhizoma Saponins ameliorate CCl4-induced liver fibrosis via modulation of the Nrf2-HO-1/NQO-1 and TGF-β1/Smads signaling pathways - Yan Hong; Shuang Geng; Huihao Ao; Mengya Fu; Xiaojun Yang; Gang Cao; Yanquan Han (Biochemistry and Biophysics Reports)
Objective/background: Paridis Rhizoma is a common traditional Chinese medicine (TCM), possessing therapeutic effects including heat-clearing, detoxification, and liver calming effects. It is frequently applied in TCM prescriptions for the treatment of liver disease. Studies have shown that total saponins derived from Paridis Rhizoma (PRS) have potent anti-liver fibrosis effect, but its mechanism in treating liver fibrosis has not been clarified. This study aimed to explore the therapeutic effect of PRS on liver fibrosis and elucidate their potential underlying pharmacological mechanisms. Methods: The targets and pathways of Paridis Rhizoma Saponins on experimental liver fibrosis were analyzed using network pharmacology and molecular docking. PRS was administered to rats with CCL4-induced liver fibrosis rats. Liver function, fibrosis, and inflammatory indicators were assessed using ELISA to measure serum AST and ALT, as well as liver tissue levels of HA, LN, Col IV, and PC-III fibrosis markers. Additionally, inflammatory markers IL-6, IL-β, and TNF-a were quantified. Liver morphological, H&E, and Masson's staining were used to observe the degree of liver fibrosis. The mRNA and protein expressions of Nrf2-HO-1/NQO-1 and TGF-β1/Smads signaling pathways in liver tissues were detected using immunohistochemistry (IHC) staining, Western blot (WB), and RT-qPCR. Results: Comprehensive network pharmacology and animal experiments show that PRS may act on STAT3, SRC, VEGFA, AKT1 and other targets through its polyphyllin I, polyphyllin II, polyphyllin VI, polyphyllin VII and other components.Analysis from ELISA showed that PRS could improve liver function, mitigate the progression of liver fibrosis, and regulate inflammatory responses in rats. Morphological, H&E, and Masson's staining demonstrated that PRS significantly improved liver tissue immune response and necrosis. Additionally, IHC staining, WB results, and RT-qPCR results showed that PRS positively regulates the Nrf2-HO-1/NQO-1 and TGF-β1/Smads signaling pathways to counteract the development of pathological liver fibrosis in rats. Conclusion: These findings indicate that PRS can mitigate the impact of CCl4-induced liver fibrosis in experimental animals by upregulating the Nrf2-HO-1/NQO-1 and downregulating the TGF-β1/Smads signaling pathways.